2021
DOI: 10.1097/ta.0000000000003374
|View full text |Cite
|
Sign up to set email alerts
|

Comparing fatal child abuse involving biological and surrogate parents

Abstract: BACKGROUND:Nearly half of pediatric homicides younger than 5 years are attributable to child abuse. Parents are most commonly the perpetrators, but less is known about incidents involving biological versus surrogate parents. We sought to evaluate the characteristics of fatal child abuse involving biological and surrogate parents using the Georgia National Violent Death Reporting System, which we believe may differ in demographics and incident characteristics. METHODS:This database was used to examine all homic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Participants for the current study included families in which biological mother–father pairs were identified as co-perpetrating maltreatment against a child and that maltreatment subsequently led to foster care entry of the same child. Although non-biological caregivers also engage in child maltreatment [ 1 ], the current study focused on biological mothers and fathers of the same child since research shows that more biological parents than non-biological parents perpetrate child maltreatment (e.g., [ 30 , 31 ]), as well as given complexities with the NCANDS data structure. Of the 729,854 relevant cases in the original NCANDS Child File dataset, there were 145,201 cases in which children were removed from their homes and entered foster care on or after the child maltreatment report date.…”
Section: Analytic Samplementioning
confidence: 99%
“…Participants for the current study included families in which biological mother–father pairs were identified as co-perpetrating maltreatment against a child and that maltreatment subsequently led to foster care entry of the same child. Although non-biological caregivers also engage in child maltreatment [ 1 ], the current study focused on biological mothers and fathers of the same child since research shows that more biological parents than non-biological parents perpetrate child maltreatment (e.g., [ 30 , 31 ]), as well as given complexities with the NCANDS data structure. Of the 729,854 relevant cases in the original NCANDS Child File dataset, there were 145,201 cases in which children were removed from their homes and entered foster care on or after the child maltreatment report date.…”
Section: Analytic Samplementioning
confidence: 99%